Metody oceny aktywności mięśnia poprzecznego brzucha stosowane w rehabilitacji = Methods of assessing the activity of the transversus abdominis muscle used in rehabilitation - Kochański, Bartosz; Kałużny, Krystian; Plaskiewicz, Anna; Ratuszek-Sadowska, Dorota; Hagner, Wojciech; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Kochański Bartosz, Kałużny Krystian, Plaskiewicz Anna, Ratuszek‑Sadowska Dorota,Hagner Wojciech, Zukow Walery. Metody oceny aktywności mięśnia poprzecznego brzucha stosowane w rehabilitacji = Methods of assessing the activity of the transversus abdominis muscle used in rehabilitation. Journal of Education, Health and Sport. 2015;5(4):81-89. ISSN 2391-8306. DOI: 10.5281/zenodo.16625 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A81-89 https://pbn.nauka.gov.pl/works/553238 http://dx.doi.org/10.5281/zenodo.16625 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02.2015. Accepted: 15.03.2015. Metody oceny aktywności mięśnia poprzecznego brzucha stosowane w rehabilitacji Methods of assessing the activity of the transversus abdominis muscle used in rehabilitation Bartosz Kochański1, Krystian Kałużny1, Anna Plaskiewicz1, Dorota Ratuszek‑Sadowska2,Wojciech Hagner1, Walery Zukow3 1Katedra i Klinika Rehabilitacji, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 2Katedra Neuropsychologii Klinicznej, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 3Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Polska Streszczenie Nowoczesny model funkcjonalny dzieli mięśnie kręgosłupa w odcinku lędźwiowym na stabilizatory lokalne, stabilizatory globalne jednostawowe oraz stabilizatory globalne wielostawowe. Grupa mięśni lokalnych zapewnia stabilność kręgosłupa poprzez tzw. napięcie wyprzedzające (feedforward). Utworzona jest przez przeponę, m. poprzeczny brzucha (TrA), włókna głębokie m. wielodzielnego lędźwi, włókna tylne m. lędźwiowego oraz m. dna miednicy. Kluczową rolę w stabilizacji i odpowiedniej kontroli ruchu kręgosłupa odgrywa miesień poprzeczny brzucha. Ocena aktywności TrA jest bardzo ważnym elementem postępowania leczniczego, ponieważ może pomóc w diagnozowaniu pacjentów oraz planowaniu terapii. W pracy przedstawiono wybrane metody oceny aktywności mięśnia poprzecznego brzucha stosowane w rehabilitacji. Słowa kluczowe: miesień poprzeczny brzucha, TrA, stabilizatory lokalne, ocena aktywności. Abstract Modern functional model divides the muscles of the lumbar spine at the local stabilizers and global stabilizers. Local muscle group provides stability to the spine by feedforward tension. Local stabilizers consist of the diaphragm, the transverse abdominal muscle (TRA), the fibers deep Multifidus muscle, fiber back of the lumbar muscle and pelvic floor muscles. An important role in the stabilization and proper spinal motion control plays a transverse abdominal muscle. Assessment TRA activity is a very important part of treatment because it can help in the diagnosis of patients and treatment programming. The paper presents selected methods for assessing the activity of the transversus abdominis muscle used in rehabilitation. Keywords: transverse abdominal muscle, TRA, local stabilizers, activity assessment.